(3Mb GdeJge ai GdOaGY NdGd eQMdI GdeMGceI (B: s (3OQGSI ebGQfI Hjf GdbGfhf GdeUQi hGdbGfhf GdEeGQGJi (B/ s - (3QGFO SYjO UGdM YHOGddg Yhdbi s; (3TQja cGeds; (3eCehf SdGeIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3Ef gPg GdSGdI JJHfi Mb GdeJge ai GdOaGY NdGd eQMdI GdeMGceI GdLRGFjI hHOCJ gPg GdOQGSI HJfGhd GdHYO GdJGQjNi dMb GdeJge ai GdOaGY NdGd eQMdI GdeMGceI GdLRGFjI Ke JfGhdJ GdeHGOF GdYGeI GdMGceI dMb GdeJge ai GdOaGY NdGd eQMdI GdeMGceI hJfGhdJ GdYdGbI Hjf Mb GdOaGY hGdeMGceI CeGe GdbVGA GdWHjYi hCUd GdHQGAI hcPdc Mbhb GdOaGY GdeJYdbI HMSf SjQ ELQGAGJ GdeMGceI GdLRGFjI Ke OQGSI hSGFd eeGQSI Mb GdeJge ai GdOaGY NdGd eQMdI GdeMGceI Ke JbOje GdOaGY hGdWdHGJ hGdGSJYGfI HeMGei chSjdI deeGQSI Mb GdOaGY eQMdI GdeMGceI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2012s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B466-486s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdOaGY Yf GdeJge s; (3Mb GdeJge s; (3eQMdI GdeMGceI s; (3GdbGfhf GdeUQjs; (3GdbGfhf GdEeGQGJj s; (3GdbVGA GdLRGFjs; (3GdbVGA GdWHjYj s; (3ebheGJ GSJbdGd GdbVGA s; (3eHOC GdHQGAI s; (3GdeMGceI GdLRGFjI s; (3YdGfjI GdeMGceI s; (3GdehGLgI s; (3GdGSJLhGH s; (3GdTahjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs